2015
DOI: 10.1021/acs.accounts.5b00312
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Oxygen Consumption with Hydrocarbon Oxidation in Bacterial Multicomponent Monooxygenases

Abstract: A fundamental goal in catalysis is the coupling of multiple reactions to yield a desired product. Enzymes have evolved elegant approaches to address this grand challenge. A salient example is the biological conversion of methane to methanol catalyzed by soluble methane monooxygenase (sMMO), a member of the bacterial multicomponent monooxygenase (BMM) superfamily. sMMO is a dynamic protein complex of three components: a hydroxylase, a reductase, and a regulatory protein. The active site, a carboxylate-rich non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 72 publications
3
53
0
Order By: Relevance
“…It has recently been established that the MMOB modulates the activity of sMMO by inducing conformational changes in the protein, thus allowing the access of dioxygen and methane to the diiron center (through a series of hydrophobic cavities) and restricting proton access to this diiron center during the formation of Fe2O2 intermediates. Moreover, the competition between MMOB and MMOR inhibits undesired electron transfer to the Fe2O2 intermediates, by blocking the binding of MMOR to MMOH during O2 activation [26,27].…”
Section: Methane Monooxygenasementioning
confidence: 99%
“…It has recently been established that the MMOB modulates the activity of sMMO by inducing conformational changes in the protein, thus allowing the access of dioxygen and methane to the diiron center (through a series of hydrophobic cavities) and restricting proton access to this diiron center during the formation of Fe2O2 intermediates. Moreover, the competition between MMOB and MMOR inhibits undesired electron transfer to the Fe2O2 intermediates, by blocking the binding of MMOR to MMOH during O2 activation [26,27].…”
Section: Methane Monooxygenasementioning
confidence: 99%
“…Although oxidoreductases capable of direct interaction with O 2 in its triplet ground state have been identified [85], the majority of native oxidase enzymes requires additional organic cofactors or redox-active transition metal centers Molecular oxygen from air is a clean, abundant and environmentally benign reagent ideally suited for substrate oxidation processes including selective C-H bond functionalization. Therefore the utilization of oxidase-like reactivity for green synthetic processes based on O 2 or H 2 O 2 is a highly desirable research goal [92][93][94].…”
Section: Activation and Reduction Of Dioxygenmentioning
confidence: 99%
“…The unique chemistry of high-valent metal oxo-species such as ferryl Fe IV =O intermediates and Mn IV -oxyl radicals plays a prominent role in some of the most difficult to achieve bioinorganic redox processes like selective alkane functionalization and photosynthetic water oxidation [92,[103][104][105][106][107]. With the help of reactive oxo and peroxo species, oxygenase enzymes can catalyze the transfer of one or two O-atoms originating from dioxygen to their substrates.…”
Section: Oxygenase Catalysis Driven By Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the carboxylatebridged dinuclear iron center is in the hydroxylase component, many reports have demonstrated that efficient hydroxylation of substrates by BMMs is not possible without both the reductase and regulatory components, which physically interact with the hydroxylase component to modulate the hydroxylation activity (Liu et al 1997;Sazinsky and Lippard 2006;Tinberg et al 2011). The regulatory protein couples oxidation of NAD(P)H to hydroxylation of the organic substrate, a process that has been characterized in sMMO and PH (Qian et al 1997;Shinohara et al 1998;Wang et al 2015). The reductase component is usually an flavin adenine dinucleotide (FAD)-and [2Fe-2S]-containing enzyme that transfers electrons from NAD(P)H to the di-iron sites of the terminal oxygenase via the [2Fe-2S] cluster and flavin prosthetic group.…”
Section: Introductionmentioning
confidence: 99%